Pengelolaan Pembelajaran Bahasa Inggris Berbasis Kurikulum Merdeka - Cuci Nur Indah Kartika Dewi; Connie (UNIVERSITAS BENGKULU, 2023)
The objective of this study is to describe the management of English Learning based on the Kurikulum Merdeka at SMPS IT Darul Fikri Argamakmur Bengkulu Utara. This research uses descriptive qualitative method. The research subjects were English teacher, principal dan vice principal of SMPS IT Darul Fikri Argamakmur Bengkulu Utara. The data research obtained from the result of interview, observation and documentation. Research data analysis were use Miles and Huberman interactive models and the result of the study were, 1) Learning plan; analysis of learning achievements which are produce organize learning objectives, flow chart learning objectives, diagnostic assessment plan, learning module, differentiated learning planning, learning assessment planning, 2) implementation of learning; pre-learning activities, core learning activities, learning approach activities which contain emotional social learning and religious specialty curriculum, 3) learning assessments; summative and formative assessments, 4) the management of English learning inhibition were limitedness of internet access, and inadequate skill of the strengthening the profile of Pancasila students project.